An Increasing Trend in the Prevalence of Polypharmacy in Sweden: A Nationwide Register-Based Study - Zhang, Naiqi; Sundquist, Jan; Sundquist, Kristina; Ji, Jianguang (Frontiers in Pharmacology, 2020)
Aim: Polypharmacy is becoming a global health problem. The aims of this study were to evaluate the temporal trends in the prevalence of polypharmacy in Sweden and to explore polypharmacy disparities by age, gender, education, and immigration status. Methods: Polypharmacy and excessive polypharmacy were evaluated using data extracted from the Swedish Prescribed Drug Register between 2006 and 2014. Polypharmacy was defined as being exposed to five or more drugs and excessive polypharmacy was defined as being exposed to 10 or more drugs during one month respectively. Average annual percent change (AAPC) was calculated using Joinpoint Statistical Software. Results: The prevalence of polypharmacy increased from 16.9% in 2006 to 19.0% in 2014 with an AAPC of 1.3; the prevalence of excess polypharmacy increased from 3.8% in 2006 to 5.1% in 2014 with an AAPC of 3.4. The prevalence of polypharmacy and excessive polypharmacy increased dramatically with age and peaked up to 79.6% and 36.4% in individuals aged 90 and above respectively. Females and individuals with lower education level were associated with a higher rate of polypharmacy and excessive polypharmacy. Immigrants from Middle-Eastern countries had the highest rate of polypharmacy and excessive polypharmacy, whereas individuals from Western Europe countries had the lowest rate. Conclusion: The prevalence of polypharmacy has increased gradually in Sweden during the past decade. Individuals with older age, female sex or lower education have a higher rate of polypharmacy and excessive polypharmacy. Immigrants from Middle-Eastern countries showed a higher rate of polypharmacy.